2015
DOI: 10.1108/srj-02-2013-0014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of award on CSR disclosures in annual reports of Malaysian PLCs

Abstract: Purpose – The paper aims to examine the determinants of corporate social responsibility (CSR) disclosures in the annual reports of Malaysian public listed companies (PLCs). In 2006, Bursa Malaysia Berhad (BMB) launched its CSR Framework (effective in 2007) which is supposed to guide the Malaysian PLCs’ CSR disclosures. It is believed that this CSR framework may influence CSR disclosures to be more systematic, yet there is no evidence whether this framework influences the extent and quality of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
106
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 50 publications
13
106
2
3
Order By: Relevance
“…Extant SD literature focusing on why companies disclose sustainability information (De Villiers & Alexander, ), have investigated its nature, patterns (e.g., Buhr & Freedman, ), and determinants (e.g., Chakroun & Matsoussi, ; El‐Halaby & Hussainey, ; Ghazali, ). In this regard, factors such as organisational characteristics, such as firm size (See Esa & Ghazali, ; Mio & Venturelli, ; Rahman, Zain, & Al‐Haj, ), profitability (See Anas, Rashid, & Annuar, ; Cowen, Ferreri, & Parker, ; El‐Halaby & Hussainey, ), industry type (See Chan, Watson, & Woodliff, ; Naser & Hassan, ; Parsa & Kouhy, ), and corporate governance mechanisms (See Haji, ; Jizi, Salama, Dixon, & Stratling, ; Khan, Muttakin, & Siddiqui, ), have been identified as key determinants of SD . Nevertheless, national institutional environmental influences upon SD , have received much less attention (Jackson & Apostolakou, ; Martínez‐Ferrero & García‐Sánchez, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant SD literature focusing on why companies disclose sustainability information (De Villiers & Alexander, ), have investigated its nature, patterns (e.g., Buhr & Freedman, ), and determinants (e.g., Chakroun & Matsoussi, ; El‐Halaby & Hussainey, ; Ghazali, ). In this regard, factors such as organisational characteristics, such as firm size (See Esa & Ghazali, ; Mio & Venturelli, ; Rahman, Zain, & Al‐Haj, ), profitability (See Anas, Rashid, & Annuar, ; Cowen, Ferreri, & Parker, ; El‐Halaby & Hussainey, ), industry type (See Chan, Watson, & Woodliff, ; Naser & Hassan, ; Parsa & Kouhy, ), and corporate governance mechanisms (See Haji, ; Jizi, Salama, Dixon, & Stratling, ; Khan, Muttakin, & Siddiqui, ), have been identified as key determinants of SD . Nevertheless, national institutional environmental influences upon SD , have received much less attention (Jackson & Apostolakou, ; Martínez‐Ferrero & García‐Sánchez, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on CSER disclosure has gained wide attention in developed countries, such as Europe and the United States. However, the level of CSER of public listed companies in Malaysia is still generally low (Anas et al 2015;Saleh et al 2010;Zainal et al, 2013). In Malaysia, CSER disclosure is a voluntary initiative mainly focused on the social and environmental aspects of companies presented in companies' annual reports to increase good governance, accountability and transparency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of CSER of public listed companies in Malaysia is still generally low (Anas et al 2015;Saleh et al 2010;Zainal et al 2013). Most previous studies on CSER by public listed companies in Malaysia found that reporting appeared to be low and restricted to general and ad-hoc statements on environmental matters (Saleh et al 2010;Zainal & Zainudin 2013).…”
Section: Cser In Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…The insignificant results of the board size, board gender and board educational confirm with prior literatures (see for example Haniffa and Hudaib 2006;Adams and Ferreira 2009;Christy, Matolcsy, Wright, & Wyatt, 2010). Additionally, the result of awards also might be inconsistent with prior studies (Anas et al, 2015;Boesso & Kumar, 2007) which revealed a significant relationship between awards and the extent of the CSR disclosure as these studies used different indices.…”
mentioning
confidence: 64%